FEATURES OF ASSESSING THE LEVEL OF INNOVATIVE DEVELOPMENT OF CONSTRUCTION ENTERPRISES - KHARCHUK, Tetiana; LOBAI, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to a comprehensive study of the specifics of assessing the innovative development of construction enterprises. It is critically important for their effective functioning in turbulence, uncertainty, and unpredictability of changes in the external environment. The paper identifies industry specifics and outlines the problems of assessing the innovative development of construction enterprises under martial law in Ukraine, which imposes additional challenges on their activities. The impact of external and internal factors on construction enterprises’ operational activities and management processes is analyzed to identify key factors that stimulate or inhibit their innovative activity. The directions of adaptation of enterprises to new realities are considered, including the transformation of production processes, the implementation of innovative technologies and materials, human resources management, optimization of financial flows, and adaptation of sales strategies. A methodological approach is proposed to assess the level of innovative development of construction enterprises. This approach considers the specifics of the industry and the peculiarities of functioning under martial law. It is based on a comprehensive analysis of their innovative potential, covering technological, labor, financial, organizational, managerial, information and communication, and marketing potentials. Implementing the proposed methodological approach involves a precise sequence of stages, including identifying industry features, resource analysis, assessment of innovative potential components, determining weight coefficients, calculation of generalizing and integral indicators, and interpretation of results for developing strategic management decisions. The study’s results can be used to identify the strengths and weaknesses of enterprises’ innovative activities, develop innovative development strategies, attract investments, select partners, and assess the effectiveness of innovative programs, especially in an unstable external environment.